1999
DOI: 10.1017/s0016672399003973
|View full text |Cite
|
Sign up to set email alerts
|

Heavy heat shock induced retrotransposon transposition in Drosophila

Abstract: The phenomenon of transposition induction by heavy heat shock (HHS) was studied. Males of a Drosophila isogenic line with a mutation in the major gene radius incompletus (ri) were treated by HHS (37 degrees C for 1 h followed by 4 degrees C for 1 h, with the cycle repeated three times) and crossed to untreated females of the same line. The males were crossed 5 d after heat shock, and also 9 d after HHS. Many transpositions were seen in the F1 larvae by in situ hybridization. The rate of induced transposition w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Several studies of D. melanogaster report transposition rates ranging from 10 -5 to 10 -3 events/copy/generation under normal conditions for retroelements (Charlesworth et al, 1992;Nuzhdin and Mackay, 1995;Suh et al, 1995;Maside et al, 2000), about 10 -2 after heat shocks (Vasilyeva et al, 1999) and up to 10 -1 in dysgenic crosses (Seleme et al, 1999). The same orders of magnitude are reported for Class II elements, in normal and dysgenic conditions (Eggleston et al, 1988;Biémont, 1994).…”
Section: Transposition Ratementioning
confidence: 99%
“…Several studies of D. melanogaster report transposition rates ranging from 10 -5 to 10 -3 events/copy/generation under normal conditions for retroelements (Charlesworth et al, 1992;Nuzhdin and Mackay, 1995;Suh et al, 1995;Maside et al, 2000), about 10 -2 after heat shocks (Vasilyeva et al, 1999) and up to 10 -1 in dysgenic crosses (Seleme et al, 1999). The same orders of magnitude are reported for Class II elements, in normal and dysgenic conditions (Eggleston et al, 1988;Biémont, 1994).…”
Section: Transposition Ratementioning
confidence: 99%
“…Previously, it had been shown that culture at this temperature does not mobilize transpositionally inactive TE families either (AlonsoGonzalez et al 2006). It has been reported that heavy heat shock induces transposition of roo (Zabanov et al 1994) and other retrotransposon families (Ratner et al 1992;Vasilyeva et al 1999), but the nature of the eVect of heat shock is, probably, diVerent from that of extreme but permissive temperatures. Above 28° takes place a considerable drop in fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Another example of variation in TE number related with natural environmental variation was given for BARE-1 in barley (Kalendar et al 2000). In Drosophila, some retrotransposons were mobilized after heat shocks in certain laboratory lines (Ratner et al 1992;Zabanov et al 1994;Vasilyeva et al 1999), while in other experiments that eVect was not found (Arnault et al 1997). Less severe thermal stresses might have some eVect on TE activity, for example high temperature enhances transposition of the P element in dysgenic crosses (Engels and Preston 1980).…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila, heat shocks amplify the amount of transcripts of the copia element, though without any association with transposition (Strand & McDonald, 1985). While some experiments showed that some retrotransposons are mobilized after heat shocks in certain laboratory lines (Junakovic et al, 1986;Ratner et al, 1992;Vasilyeva, Bubenshchikova & Ratner, 1999), other results showed no effect under similar stresses (Arnault, Loevenbruck & Bie´mont, 1997). In D. melanogaster, high temperature enhances transposition of the P element in dysgenic crosses (Engels & Preston, 1980).…”
Section: Introductionmentioning
confidence: 99%